(untitled) (Research, Society and Development, 2021)
Objective: describe the incidence and distribution of acquired syphilis cases in Passo Fundo (Rio Grande do Sul) between 2010 and 2017. Methods: transversal descriptive study, realized in the Health Surveillance Sector of the Municipal Health Secretariat. Were included the notifications that were available on SINAN. The analysis occurred descriptively, with the SPSS program 18th version, through the notifications distribution in sociodemographic variables. Results: 2.424 acquired syphilis notifications were computed. An expressive growth in the notifications number was observed during the study time. Most of the diagnosis were in men (51,8%), white people (82,4%) and in persons with unfinished Elementary and Middle School (18,4%) and with finished High School (24,1%). Conclusion: this study highlights the importance of studies in the countryside of Brazil, the need of newer investigations so to understand better the factors related to the big number of syphilis cases in the city.